Topologically Closed Packed Phase and Its Interaction with Dislocation Movement in Ni–Based Superalloy during High–Temperature Creep - Wenqi Guo; Haigen Zhao; Yi Ru; Yanling Pei; Junwu Wang; Qiaomu Liu; Xuehang Li; Haibo Wang; Shuangqi Zhang; Shengkai Gong; Shusuo Li (Crystals, 2022)
In superalloys, topologically close–packed (TCP) phases, which contain refractory elements, usually significantly influence the mechanical properties. The current work investigates the structure and composition of the TCP phase in an Al–Mo–rich Ni–based single crystal superalloy. It is shown that after 40 h of thermal exposure, a large number of strip–like TCP phases are formed, which are enriched in Mo and Re. The structure of the TCP phase is identified as the tetragonal σ phase with the lattice parameter a being 0.93 nm and c being 0.50 nm. During the creep process, the single crystal tilts obviously and leads to orientation variation from <1 1 0> direction. Two groups of dislocations are observed in the deformed sample. One group contains straight dislocation lines and another group contains dislocation networks. The interaction between TCP phase and dislocation in the single crystal superalloy is studied to reveal the effect of the TCP phase on the deformation behavior. During creep, the σ phase hinders the dislocation movement, which may contribute to the propagation of the cracks and the final fracture.